2007
DOI: 10.1111/j.1365-2982.2007.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the association of adrenergic and serotonergic genotype and gastrointestinal motor functions

Abstract: Adrenergic and serotonergic mechanisms alter human gut motor functions. Genotype variation influences phenotype. Our aim was to test the hypothesis that variation in genes that control these functions is associated with gastrointestinal (GI) motor functions in humans with functional GI disorders (FGID). A database of 251 people was assembled by combining genotype data with measurements of gut transit and gastric volumes. Genetic variations evaluated were: alpha(2A) adrenergic (C-1291G), alpha(2C) (Del 332-325)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…In a previous study (22), we also observed significant association between GN␤3 genotype and gastric emptying of solids at 4 h. The physiological factors that are significantly associated with the development of postprandial symptoms in dyspepsia are fasting gastric volume and accelerated gastric emptying at 1 h and delayed gastric emptying at 4 h (18). Together with the previous study (22), our present observations on the association of GN␤3 genotype and fasting gastric volume are consistent with the hypothesis that the epidemiological association of GN␤3 genotype with dyspepsia may be related to an association with abnormal gastric functions.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In a previous study (22), we also observed significant association between GN␤3 genotype and gastric emptying of solids at 4 h. The physiological factors that are significantly associated with the development of postprandial symptoms in dyspepsia are fasting gastric volume and accelerated gastric emptying at 1 h and delayed gastric emptying at 4 h (18). Together with the previous study (22), our present observations on the association of GN␤3 genotype and fasting gastric volume are consistent with the hypothesis that the epidemiological association of GN␤3 genotype with dyspepsia may be related to an association with abnormal gastric functions.…”
Section: Discussionmentioning
confidence: 54%
“…We have previously observed associations of the same genetic variations with gastric emptying in 251 participants (60 male and 191 female): 82 healthy, 20 patients with IBS with mixed bowel habit, 49 IBS-C, 67 IBS-D, and 33 functional dyspepsia (22). Those participants were selected from a database of people who had undergone gastrointestinal motility tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacotherapy for IBS-D: serotonin receptor antagonists Because more than 95% of the body's serotonin is located in the gastrointestinal tract and 5-HT 3 and 5-HT 4 receptor manipulation has been shown to alter gastrointestinal transit (for example, with alosetron and tegaserod), [108][109][110] serotonin is a viable therapeutic target. A randomized crossover trial published in 2013 assessed whether ondansetron, a 5HT 3 receptor antagonist traditionally used for nausea and vomiting, would be useful because of its constipating effect.…”
Section: Standard or Individualized Chinese Herbal Formulamentioning
confidence: 99%